Endotoxaemia-augmented murine venous thrombosis is dependent on TLR-4 and ICAM-1, and potentiated by neutropenia - Obi, Andrea T.; Andraska, Elizabeth; Kanthi, Yogendra; Kessinger, Chase W.; Elfline, Megan; Luke, Cathy; Siahaan, Teruna J.; Jaffer, Farouc A.; Wakefield, Thomas W.; Henke, Peter K. (Thrombosis and Haemostasis, 2017)
Venous thromboembolism is a major cause of death during and immediately post-sepsis. Venous thrombosis (VT) is mediated by cell adhesion molecules and leukocytes, including neutrophil extracellular traps (NETs). Sepsis, or experimentally, endotoxaemia, shares similar characteristics and is modulated via toll like receptor 4 (TLR4). This study was undertaken to determine if endotoxaemia potentiates early stasis thrombogenesis, and secondarily to determine the role of VT TLR4, ICAM-1 and neutrophils (PMNs). Wild-type (WT), ICAM-1-/- and TLR4-/- mice underwent treatment with saline or LPS (10 mg/kg i.p.) alone, or followed by inferior vena cava (IVC) ligation to generate stasis VT. In vivo microscopy of leukocyte trafficking was performed in non-thrombosed mice, and tissue and plasma were harvested during early VT formation. Pre-thrombosis, circulating ICAM-1 was elevated and increased leukocyte adhesion and rolling occurred on the IVC of LPS-treated mice. Post-thrombosis, endotoxaemic mice formed larger, platelet-poor thrombi. Endotoxaemic TLR4-/- mice did not have an augmented thrombotic response and exhibited significantly decreased circulating ICAM-1 compared to endotoxaemic WT controls. Endotoxaemic ICAM-1-/- mice had significantly smaller thrombi compared to controls. Hypothesising that PMNs localised to the inflamed endothelium were promoting thrombosis, PMN depletion using anti-Ly6G antibody was performed. Paradoxically, VT formed without PMNs was amplified, potentially related to endotoxaemia induced elevation of PAI-1 and circulating FXIII, and decreased uPA. Endotoxaemia enhanced early VT occurs in a TLR-4 and ICAM-1 dependent fashion, and is potentiated by neutropenia. ICAM-1 and/or TLR-4 inhibition may be a unique strategy to prevent sepsis-associated VT.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: TLR4; cellular adhesion molecules; ICAM-1; sepsis; LPS; venous thrombosis; venous thromboembolism